2020
DOI: 10.1093/nsr/nwaa032
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting trends of PM2.5 and surface-ozone concentrations in China from 2013 to 2017

Abstract: Although much attention has been paid to investigating and controlling air pollution in China, the trends of air-pollutant concentrations on a national scale have remained unclear. Here, we quantitatively investigated the variation of air pollutants in China using long-term comprehensive data sets from 2013 to 2017, during which Chinese government made major efforts to reduce anthropogenic emission in polluted regions. Our results show a significant decreasing trend in the PM2.5 concentration in heavily pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
126
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(137 citation statements)
references
References 41 publications
5
126
1
5
Order By: Relevance
“…The formation of tropospheric ozone is relatively complex, influenced on the one hand by solar radiation and on the other by the concentration of other atmospheric pollutants ( Wang et al, 2017 ). In recent years, there has been a general decrease in PM 2.5 in China's major cities ( Ding et al, 2019 ; Li et al, 2019 ; Zhang et al, 2019 ), but a certain increase in tropospheric O 3 ( Chan et al, 2017 ; Chan et al, 2018 ; Wang et al, 2020b ). PM 2.5 has a very large impact on visibility and is therefore more likely to be of public concern.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of tropospheric ozone is relatively complex, influenced on the one hand by solar radiation and on the other by the concentration of other atmospheric pollutants ( Wang et al, 2017 ). In recent years, there has been a general decrease in PM 2.5 in China's major cities ( Ding et al, 2019 ; Li et al, 2019 ; Zhang et al, 2019 ), but a certain increase in tropospheric O 3 ( Chan et al, 2017 ; Chan et al, 2018 ; Wang et al, 2020b ). PM 2.5 has a very large impact on visibility and is therefore more likely to be of public concern.…”
Section: Introductionmentioning
confidence: 99%
“…As the symbol of modern civilization and social progress, cities are the major centers of population, economic and social development. Compared to rural areas, the problem of compound air pollution in urban regions has received increasing attention in recent decades due to the numerous emission sources and focused intensity of pollutants ( Li et al, 2019b , 2019c ; Song et al, 2017 ; Wang et al, 2014b , 2020d ). As one of the countries with the fastest economic development in the world, the urbanization in China is rapidly developing, resulting in groups of megacities with permanent residents exceeding 10 million, around which urban agglomeration has evolved in areas such as the North China Plain (NCP), Yangtze River Delta (YRD), and Pearl River Delta (PRD).…”
Section: Introductionmentioning
confidence: 99%
“…In September 2013, the State Council issued the Action Plan for Prevention and Control of Air Pollution , demanding that PM 10 concentrations decrease by more than 10% in 2017 compared to the level in 2012 in cities at the prefectural level and above; additionally, a target number of excellent and good days with an air quality index (AQI) less than 100 was required, following the China Environmental Protection Standard ‘HJ 633-2012’ ( http://www.gov.cn/zhengce/content/2013-09/13/content_4561.htm ). Noticeably, these regulatory measures have resulted in significant reduction in primary PM emissions, but the secondary pollutant ozone (O 3 ) remains prominent ( Huang et al, 2021 ; Li et al, 2019b ; Wang et al, 2020d ; Zeng et al, 2019 ). Numerous studies have indicated that compound air pollution has resulted from the primary pollutants emitted by industry, power plants, traffic and heating processes and from the secondary pollutants generated by complex physical, chemical and biological processes ( An et al, 2019 ; Fenger, 2009 ; Guo et al, 2020 ; Li et al, 2019c ; Zhang et al, 2020 ; Zhu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is a contrasting trend of O 3 and PM 2.5 in China. In contrast to the above-mentioned increase in O 3 , PM 2.5 in eastern China has seen an annual decrease of around 7% from 2013 to 2017 11 , 12 . It suggests that knowledge and experiences in PM 2.5 are not necessarily applicable to O 3 .…”
Section: Introductionmentioning
confidence: 71%